A recombinant fusion protein derived from dog hookworm inhibits autoantibody‐induced dermal–epidermal separation ex vivo. Issue 11 (21st August 2015) - Kemmer, Annette; Bieber, Katja; Abadpour, Aida; Yu, Xinhua; Mitschker, Nina; Roth, Sara; Kauderer, Claudia; Ludwig, Ralf J.; Seeger, Karsten; Köhl, Jörg; Zillikens, Detlef; Recke, Andreas
Abstract: The proteins secreted by parasitic nematodes are evolutionarily optimized molecules with unique capabilities of suppressing the immune response of the host organism. Neutrophil inhibitory factor (NIF), which is secreted by the dog hookworm Ancylostoma caninum, binds to the β 2 integrin CD11b/CD18, which is expressed on human neutrophils, eosinophils, monocytes and macrophages and inhibits neutrophil‐dependent lung injury and neutrophil invasion of ischaemic brain tissue. Neutrophils are key players in the pathogenesis of subepidermal autoimmune blistering diseases (sAIBDs), and their pathogenic activities are crucially dependent on β 2 integrin functionality. Based on the template of single‐stranded, dimerizing antibody derivatives, which are already used in cancer treatment, we designed a novel biologic, NIF‐IGHE‐CH4, comprising NIF and the dimerizing but otherwise inert constant heavy subdomain 4 (CH4) of human IgE (IGHE). This molecule was evaluated in a variety of in vitro assays, demonstrating its ability to inhibit pathogenically relevant neutrophil functions such as migration, adhesion and spreading, and release of reactive oxygen species. Finally, we confirmed that NIF‐IGHE‐CH4 inhibits blister formation in an ex vivo assay of sAIBD. These results suggest that NIF‐IGHE‐CH4 is a novel potential anti‐inflammatory drug for the treatment of neutrophil‐mediated diseases such as sAIBDs. This study promotes the drugs from bugs concept and encourages further research and development focused on turning parasite proteins into useful anti‐inflammatory biologics.